ChemInform Abstract: Sodium Iodide/tert‐Butyl(dimethyl)silyl Chloride‐Induced Isomerization of 2, 3‐Allenols to 2(E)‐Enals. Issue 37 (16th September 2014) - Zeng, Rong; Ma, Zhichao; Fu, Chunling; Ma, Shengming
Abstract This reaction proceeds with high stereoselectivity to give the title compounds in moderate to good yields.